Hubungan Intensitas Penggunaan Media Sosial dengan Tingkat Kesepian pada Mahasiswa Digital (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
The development of digital technology, particularly social media, has brought significant changes to human social interaction patterns. Although the ease of digital communication offers various advantages, in reality, it does not always reduce feelings of loneliness. This study aims to analyze the relationship between the intensity of social media use and loneliness levels among students in the digital era. The method used in this research is a quantitative approach with a correlational design, involving 120 active students as the sample. To measure the variable of social media use intensity, the Social Media Intensity Scale was used, while loneliness levels were measured using the UCLA Loneliness Scale. The data analysis results showed a significant positive relationship between the intensity of social media use and loneliness levels among students. This means that the higher the intensity of students' social media use, the higher the loneliness they feel. These findings provide important insight that, despite social media facilitating easier interactions, excessive use does not always positively affect the quality of social relationships. On the contrary, high social media use intensity can be associated with greater feelings of loneliness, indicating the need for a deeper understanding of the impact of social media use on individuals' emotional well-being.